Walking and perception of green space among older adults in Japan: subgroup analysis based self-efficacy. (7th January 2023) - Encho, Haruhi; Uchida, Kazuaki; Horibe, Kana; Nakatsuka, Kiyomasa; Ono, Rei
Summary: Self-efficacy is the key factor for promoting physical activity. Older adults with low self-efficacy tend to be physical inactive than those with high self-efficacy, and an approach is needed to promote physical activity. Among several approaches, increasing the perception of green space may be an effective approach for low self-efficacy not high self-efficacy, but no study has investigated. This study investigated the association between walking and perception of green space among older adults with high and low self-efficacy, respectively. We conducted a cross-sectional study among 204 community-dwelling older adults (mean age = 78.3 years, 62.3% females). Using the median split, the participants were divided into high and low self-efficacy groups based on the median score of 12. Walking was measured using the International Physical Activity Questionnaire and 'more walking' was defined as ≥150 min of walking time per week. Perception of green space was measured using an 8-item questionnaire. We performed logistic regression analysis to investigate the association between walking and perception of green space adjusted for age, gender, years of education, living with someone and income level. For all participants, 94 participants (46.1%) fell under low self-efficacy. After adjustment, higher perception of green space is associated with more walking among older adults with low self-efficacy [adjusted odds ratio (aOR) = 1.07, 95% confidence interval (CI) = 1.00–1.15], but not among those with high self-efficacy (aOR = 1.09, 95% CI= 0.99–1.20). To increase perception of green space, experts should design/improve green spaces considering beneficiaries' characteristics. Lay Summary: Low self-efficacy has a negative effect on Activities of Daily Living and Quality of Life through physical inactivity among older adults. Encouraging physical activity among those with low self-efficacy can help solve the problem, but individual intervention towards low self-efficacy requires great effort. Therefore, we focused on environmental factors as they affect more people, and investigated the association between perception of green space and walking among older adults with high and low self-efficacy, respectively. This cross-sectional study was conducted among community-dwelling older adults in Japan, the variables used in this study were asked by a questionnaire. We examined whether older people who have higher perception of green space do more walking. As a result of the analysis, high perception of green space was associated with more walking among community-dwelling older adults with low self-efficacy, but not among older adults with high self-efficacy. This result may lead to solves the problem of physical inactivity in older adults with low self-efficacy from the perspective of environmental factors. To increase perception of green space, experts such as urban planners and policy makers should design/improve green spaces considering beneficiaries' characteristics such as quantity, quality and accessibility.